Akses Keadilan bagi Masyarakat Rentan: Studi Sosio-Legal di Desa Janapria, Kabupaten Lombok Tengah - Ramdani, Muhammad Fajar; Lestari, Aisyah (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2024)
Access to justice is a fundamental prerequisite for ensuring the protection of citizens’ rights, particularly for vulnerable communities in rural areas. This study aims to analyze access to justice for vulnerable groups in Janapria Village, Central Lombok Regency, using a socio-legal approach. The research applies a qualitative empirical method through in-depth interviews, non-participant observation, and document analysis. Research subjects include vulnerable community members, village officials, community leaders, and legal aid facilitators. Data were analyzed thematically to identify patterns and dynamics of access to justice at the village level. The findings reveal that access to justice for vulnerable communities in Janapria Village remains limited. The main barriers include low legal literacy, economic constraints, unequal distribution of legal aid services, and cultural factors that discourage engagement with formal legal institutions. Communities tend to resolve legal issues through informal mechanisms that do not always ensure fair rights protection. Village officials and community-based paralegals play a crucial role, yet their effectiveness is constrained by limited legal capacity. This study concludes that improving access to justice at the village level requires an integrated strategy that combines legal literacy enhancement, equitable legal aid provision, and the strengthening of local actors. The socio-legal approach proves relevant in formulating contextual and sustainable access to justice policies for vulnerable rural communities.